My patient might be depressed – can I still screen for MCI? Exploring cognitive performance on the MoCA in older people screened for depressive symptoms with the PHQ-9 - Bösl, Sophia; Scheerbaum, Petra; Grässel, Elmar; Kessler, Christian; Scheuermann, Julia-Sophia (BMC Geriatrics, 2025)
Objective: The aim of this study was to compare the Montreal Cognitive Assessment (MoCA) performances of people who report no, subclinical, and clinical symptoms of depression. Methods: Data was collected for the randomized controlled trial BrainFit-Nutrition. A secondary data analysis of 1,111 participants (age ≥ 60 years; M = 68.4 years; 55.1% female) was performed. Depressive symptoms were assessed with the Patient Health Questionnaire-9 (PHQ-9), cognitive performance was assessed via the MoCA. Performance differences were tested with Kruskal-Wallis tests. Two sensitivity analyses were conducted, one with data from people with MCI and one with the original item structure of the MoCA. Results: No differences were found in the MoCA total score or in visuospatial, executive functioning, attention, memory, or orientation subscores between individuals with no, subclinical, or clinical symptoms of depression. A sensitivity analysis also showed no differences. Conclusion: Cognitive screening with the MoCA seems to be robust against depression and could therefore be used to screen for MCI regardless of depression level. Trial registration: The study was prospectively registered at the International Standard Randomized Controlled Trial Number Registry on 23/11/2021 (ISRCTN 10560738).
CRIS-Team Scopus Importer:2025-05-30
Keywords: Cognitive performance; Depressive symptoms; MoCA; Older people